Relationship sensitive consequentialism Is regrettable - Forcehimes, Andrew T. (2022)
Personal relationships matter. Traditional Consequentialism, given its exclusive focus on agent-neutral goodness, struggles to account for this fact. A recent variant of the theory—one incorporating agent-relativity—is thought to succeed where its traditional counterpart fails. Yet, to secure this advantage, the view must take on certain normative and evaluative commitments concerning personal relationships. As a result, the theory permits cases in which agents do as they ought, yet later ought to prefer that they had done otherwise. That a theory allows such cases is a serious defect. We thus conclude that, in terms of how the theories handle personal relationships, agent-relative consequentialism fairs no better than its traditional counterpart.